2017
DOI: 10.1111/evj.12737
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic discrimination of ataxia in horses is facilitated by blindfolding

Abstract: Summary Background Agreement among experienced clinicians is poor when assessing the presence and severity of ataxia, especially when signs are mild. Consequently, objective gait measurements might be beneficial for assessment of horses with neurological diseases. Objectives To assess diagnostic criteria using motion capture to measure variability in spatial gait‐characteristics and swing duration derived from ataxic and non‐ataxic horses, and to assess if variability increases with blindfolding. Study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, inability to detect small levels of improvement are inherent to the relatively crude and subjective assessment of ataxia using the modified Mayhew scale. Further development of objective tools of gait analysis to detect ataxia and minor differences remains an important area of development in equine neurology 36‐39 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inability to detect small levels of improvement are inherent to the relatively crude and subjective assessment of ataxia using the modified Mayhew scale. Further development of objective tools of gait analysis to detect ataxia and minor differences remains an important area of development in equine neurology 36‐39 …”
Section: Discussionmentioning
confidence: 99%
“…It is a sensitive parameter that can detect and quantify uncoordinated movements during walking. Regularity measures the stride to stride variability (which is also determined using other kinematic methods) as overground motion capture for differentiation between horses with and without ataxia [31]. In the current study, the administration of the combination of drugs induced a greater but not significant decrease in regularity values 5 min after the injection; however, from that moment onwards, all decreases in regularity were more pronounced in the detomidine group, with a longer duration of gait deficits (in the first 90 min) than the combination group (in the first 45 min) and with significant differences at 60 and 75 min.…”
Section: Discussionmentioning
confidence: 99%
“…There are well-established methods and models for data collection and interpretation within different pathologies in people ( 16 ), highlighting that instrumentation of gait using digital technologies provides objective and subtle information that is not possible to detect from clinical observation alone. For quadrupeds, objective assessment of ataxia gait patterns was studied in Olsen et al ( 17 ). It was found that motion capture can objectively aid the assessment of horses with ataxia; moreover, blindfolding of horses facilitates the discrimination of ataxic patterns.…”
Section: Introductionmentioning
confidence: 99%